Empathy and cultural competence in clinical nurses: A structural equation modelling approach - Zarei, Bahare (Nursing ethics, 2019)
Background:Forgiveness has the potential to resolve painful feelings arising from nurse–patient conflicts. It would be useful to evaluate direct and indirect important factors which are related to forgiveness in order to design interventions that try to facilitate forgiveness.Aim/objective:The purpose of this study was to evaluate the intermediating role of empathy in the cultural competence–forgiveness association among nurses using structural equation modeling.Research design:The research applied a cross-sectional correlational design.Participants and research context:The study included 380 nurses eight hospitals in southern Iran.Ethical considerations:The Ethics and Research Committee of Birjand University of Medical Sciences approved the study protocol. The voluntary nature of participation was explained consent was obtained from participants, and anonymity was guaranteed.Findings:Most of the participants were married and female and fell in the 20- to 30-year-old category. Most of them (89.5%) had a working experience of 1–10 years. The proposed model showed that nurses’ empathy intermediated the association between nurses’ cultural competence and forgiveness which has fitted the data acceptably (root mean square error approximation = 0.070; comparative fit index = 0.993; goodness-of-fit index = 0.983; and χ2/df = 2.85).Conclusion:Empathy skills and cultural competence training were essential for interventions aimed at increasing the tendency to forgive patients. In such interventions, planners should aim at increasing nurses’ cultural competence in order to enhance their empathy toward patients, which can, in turn, lead to a greater wish to forgive patients.